Narrative inquiry in disaster research: an examination of the use of personal stories from the child survivors of the 2004 Aceh tsunami - Rahiem, Maila D.H.; Ersing, Robin; Krauss, Steven Eric; Rahim, Husni (Elsevier, 2021)
This paper reviews the use of narrative inquiry in disaster research and explores how narrative inquiry could benefit the field of disaster science, inform policy, and plan for disaster prevention and intervention. The researchers critically examined their own previous experience of using a narrative approach to analyze the vulnerability and resilience of the child tsunami survivors and looked at the benefits of this approach compared to other methods. The data showed that: 1) narratives describe complex situations and explain what, why, and how something has happened; 2) narratives are one of the best possible methods for the study of children's experiences; 3) narratives provide cross-disciplinary connections that enrich the analysis; 4) narratives provide a voice to silent communities whose voices have never been heard before; 5) narratives communicate people's feelings and lives, including both their silent and non-verbal languages; 6) narratives provide rich and in-depth information. Narrative disaster research provides the opportunity to learn more about both the person and society by introducing a human voice into what has primarily been a technical field. This has important implications for policymakers to better understand the vulnerability and resiliencies from first-hand accounts of those who experienced the disaster. It is therefore a valuable research method because it has the ability to help engage the community and inform policy makers.